YIELD OF PLAIN FILM RADIOGRAPH IN THE DIAGNOSIS OF OSTEOMYELITIS IN PATIENTS WITH DIABETIC FOOT IN A TERTIARY CARE HOSPITAL - Ali, Zafar; Faheem, Muhammad; Alam, Intekhab; Taqweem, Muhammad Amjad (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the yield of plain film radiograph (PFR) in the diagnosis of osteomyelitis in patients with diabetic foot in a tertiary care hospital. Material and Methods: This hospital based non-interventional, descriptive study was conducted on 60 patients. Patients of both sexes, above the age of 12 years who were known diabetics and were clinically thought of osteomyelitis were included in the study. These patients were admitted in medical wards of Post Graduate Medical Institute, Lady Reading Hospital Peshawar, from January to December 2002. Patients were selected by non-probability convenient sampling method after obtaining an informed consent. Results: Out of 60 patients, 14 (23.33%) were having type 1 Diabetes Mellitus (DM) and 46 (76.66%) patients were having type 2 DM. Age of the patients ranged from 24 to 75 years, with a mean age of 52.4 years. Twelve patients (20%) had history of trauma and 21 (35%) patients had ill-fitting shoes, as risk factors for diabetic foot. Conclusion: Plain film radiograph detected changes of osteomyelitis in 37 (62.57%) of patients, with a sensitivity of (77.08%) and specificity of about 75%. Plain film radiograph yields valuable anatomical information at a lower cost. It has a reasonably good detection power and its easy availability even at primary and secondary care centers makes it the imaging of first choice in the study of diabetic foot. It could be followed by a three-phase bone scan and additional imaging as and when needed.